Crypto Assets in Indonesian Inheritance Law: Balancing Ownership Rights and Access Challenges - Mikael Alvaro; Mia Hadiati (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The emergence of crypto assets as a form of digital wealth has generated new legal challenges within the Indonesian inheritance law framework, particularly concerning assets stored in unmanaged wallets. This study examines the legal status of crypto assets as inheritable property and explores the legal and technical barriers associated with their transfer to heirs. Employing a normative legal research method, the study applies statutory, conceptual, analytical, and comparative approaches. The findings demonstrate that crypto assets may be classified as inheritable property because they possess economic value, are transferable, and constitute intangible movable assets within the meaning of Article 499 of the Indonesian Civil Code. Nevertheless, the inheritance of crypto assets presents significant challenges, including the loss of access to private keys, difficulties in establishing ownership due to the pseudonymous nature of blockchain technology, and jurisdictional complexities arising from cross-border transactions. These issues may hinder the effective transfer of digital wealth and potentially undermine the rights of heirs. Accordingly, the study highlights the need for a specific legal framework governing the inheritance of crypto assets in order to ensure legal certainty, facilitate asset accessibility, and protect heirs’ rights in the evolving digital economy.